Response of guanacos Lama guanicoe to changes in land management in Península Valdés, Argentine Patagonia: Conservation implications - Burgi, Maria Virginia (2012)
The guanaco Lama guanicoe was the only large native herbivore widely distributed across Patagonia until the introduction of domestic sheep Ovis aries. Guanacos have declined because of competition with sheep for forage, high hunting pressure and habitat degradation. Península Valdés is a protected area where sheep ranching is the predominant activity. A ranch formerly dedicated to sheep production was converted into a private wildlife reserve, from which all the sheep were removed in 2005. We studied changes in guanaco abundance inside and outside the reserve after sheep removal, and also plant cover of various vegetation types. We found that guanaco abundance was higher inside than outside the reserve, and increased by three-fold within 3 years. Total plant cover and grass cover were higher inside than outside the reserve. Our results showed that guanacos reacted rapidly to changes in management, and suggest that even at a high density guanacos would not be as damaging to the vegetation as sheep. Although management changes resulted in significant changes in guanaco abundance locally, the size of a protected area influences the persistence of wild populations. A large herbivore such as the guanaco needs to be managed across large areas. We believe it is necessary to implement a management plan for Península Valdés that allows for the coexistence of sustainable livestock production and healthy wildlife populations. © 2012 Fauna & Flora Internationa.